2021
DOI: 10.1371/journal.pone.0257820
|View full text |Cite
|
Sign up to set email alerts
|

The effect of horseshoes and surfaces on horse and jockey centre of mass displacements at gallop

Abstract: Horseshoes influence how horses’ hooves interact with different ground surfaces, during the impact, loading and push-off phases of a stride cycle. Consequently, they impact on the biomechanics of horses’ proximal limb segments and upper body. By implication, different shoe and surface combinations could drive changes in the magnitude and stability of movement patterns in horse-jockey dyads. This study aimed to quantify centre of mass (COM) displacements in horse-jockey dyads galloping on turf and artificial tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 110 publications
2
14
0
Order By: Relevance
“…Nevertheless, at gallop when the accelerations and loads are amplified, even small differences could be relevant for injuries and safety. In fact, the findings here tie in with the horse and jockey centre of mass displacements, which indicated that the largest vertical displacement differences were present between barefoot-artificial and steel-turf [85]. This suggests that hoof kinematic patterns are translated into upper body kinematics.…”
Section: Impactsupporting
confidence: 66%
See 4 more Smart Citations
“…Nevertheless, at gallop when the accelerations and loads are amplified, even small differences could be relevant for injuries and safety. In fact, the findings here tie in with the horse and jockey centre of mass displacements, which indicated that the largest vertical displacement differences were present between barefoot-artificial and steel-turf [85]. This suggests that hoof kinematic patterns are translated into upper body kinematics.…”
Section: Impactsupporting
confidence: 66%
“…In addition, previous comparisons between contralateral and ipsilateral pairs of limbs found that the leading forelimb and non-leading hindlimb were at greater risk [41]. Data from this study suggest the leading limbs experience the largest accelerations on the tracks used here, which had only a very slight anticlockwise bend [85]. Based on EMMs for surface effects (Table 3) averaged across all acceleration axes, the leading limbs had accelerations that were 1.5 times larger than the non-leading limbs.…”
Section: Impactsupporting
confidence: 44%
See 3 more Smart Citations